KINETICS OF ADSORPTION OF HEAVY METALS (IRON) FROM TEXTILE INDUSTRY WASTE USING CALCIUM CARBIDE RESIDUE AS ADSORBENT - Muhammad Arief Karim; Netty Herawati; Henny Juniar (Reaktor, 2022)
This research was conducted to study the efficiency of residual calcium carbide as an adsorbent using a batch process to remove iron (II) from textile industrial waste. In this study, the iron (II) content in textile industrial waste was synthetically made using . The effluent was characterized using a standard method (atomic absorption spectrometry), while the functional groups responsible for the Adsorption of iron to the surface of the calcium carbide residue were observed using SEM and Fourier Transform Infra-red (FTIR). The SEM findings revealed a highly porous morphology. FTIR revealed the presence of various functional groups (OH, CH, C=C, and C-C). Factors affecting Adsorption, eg, contact time, adsorbent dose, pH, and iron concentration, were also studied. The maximum iron (II) ion adsorption was observed to occur at pH 6. Kinetic studies showed a good correlation and best suited the pseudo-second-order kinetic model. Langmuir and Freundlich's isotherm model was used to describe the Adsorption of iron (II) on calcium carbide residues. The data obtained from the adsorption process most closely matched the Langmuir model with a correlation value of R^2 = 0.9959 and q_e=1.697 mg/g. with a pseudo-second-order kinetic model with a correlation coefficient value (R2), which is 0.9962 for an adsorbent mass of 7.5 g. The Adsorption of iron ions from textile wastewater synthesis solution using calcium carbide residues shows a physisorption mechanism.